Studi Literatur: Implementasi Pendidikan Inklusi Di Sekolah Dasar Di Provinsi Riau - Mega Julia; Rahmat Rael Mukrom; Siti Rabiah; Hendri Marhadi (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Inclusive education is an effort to create equal access to education for all individuals. Implementation of the inclusion approach in elementary schools is still faced with various challenges such as a lack of understanding about inclusive education, a curriculum that is not yet flexible for children with special needs, and minimal participation by parents and the community in inclusive education. This research aims to determine the implementation of inclusive education in elementary schools in Riau province. This research uses the Systematic Literature Review (SLR) method to collect and analyze relevant literature. Of the 4,820 articles identified, 9 key articles were selected for further analysis. The results of the research review show that the implementation of inclusive education in the schools studied shows a strong commitment, such as developing inclusion programs, individual learning programs, and providing special accompanying teachers as well as the dedication and creativity of teachers in teaching children with special needs. The challenges faced include stigma and discrimination against children with special needs, inadequate facilities and infrastructure, teacher competency that needs to be improved, and lack of coordination from various parties implementing inclusive education. Conclusion of research on the implementation of inclusive education in Riau province is still in the developing stage and requires attention and support from all parties.